EXPRESSING NON-LITERARY CONSONANT SOUNDS IN PROBLEM TEXTS - Uralov Elyor Normanovich (Western European Studies, 2024)
This article examines non-literary consonants found in problematic texts and their connection with the thematic nature of the text. It provides substantiated concepts for determining the stages of analysis and determining their practical and theoretical solutions in accordance with the object of linguistic examination. The basics of analysis of written and oral texts on various topics are outlined.
Keywords: non-literary consonants; problematic; linguistic examination